Recruitment of Captive‐Reared Florida Grasshopper Sparrows After Translocation: Age of Release Matters - Juan C. Oteyza; Karl E. Miller; Andrew Schumann; Sarah Biesemier; Andrea Sylvia (Ecology and Evolution, 2025)
ABSTRACT Translocation of animals raised in conservation breeding facilities is frequently used as a conservation tool, but few studies have assessed the age of release that maximizes recruitment post‐translocation. For birds, holding captive‐reared juveniles through their first winter is often believed to increase survival by sheltering them from expected high mortality in the wild. However, extended care in captivity requires time and expense and can be associated with the development of tame behaviors; those costs should be weighed against potential benefits. As part of a strategic conservation program for the endangered Florida grasshopper sparrow (Ammodramus savannarum floridanus), we released 265 sparrows raised under managed care into the Three Lakes Wildlife Management Area population in Florida during 2019–2021. Thirty‐two of 181 (18%) sparrows released as hatch‐years recruited (i.e., were confirmed to be paired and breeding), whereas only 4 of 84 (5%) sparrows released as second‐years recruited. Logistic regression analysis found support for release age class and mass on recruitment probability, but release age class was the only variable included in all the top three models. Based on the most‐parsimonious model, when mass was held at its mean value (16.47 g), the odds of recruitment for hatch‐year birds were 4.65 times (95% CI: 2.04, 11.75) that of second‐year birds. Despite being translocated only a few weeks before the onset of breeding, second‐year birds failed to recruit into the breeding population at rates comparable to individuals translocated 6–8 months earlier as nutritionally independent fledglings. It is unclear whether low recruitment for older sparrows was the result of higher mortality or dispersal. We discuss potential reasons why younger Florida grasshopper sparrows may be developmentally better suited to adapt to novel environments and recommend more research on the role of neuroplasticity during early learning periods and its influence on translocation outcomes.